Dynamics and energetics of the mammalian phosphatidylinositol transfer protein phospholipid exchange cycle - Grabon, Aby (J Biol Chem, 2017)
Phosphatidylinositol-transfer proteins (PITPs) regulate phosphoinositide signaling in eukaryotic cells. The defining feature of PITPs is their ability to exchange phosphatidylinositol (PtdIns) molecules between membranes, and this property is central to PITP-mediated regulation of lipid signaling. However, the details of the PITP-mediated lipid exchange cycle remain entirely obscure. Here, all-atom molecular dynamics simulations of the mammalian StART-like PtdIns/phosphatidylcholine (PtdCho) transfer protein PITPα, both on membrane bilayers and in solvated systems, informed downstream biochemical analyses that tested key aspects of the hypotheses generated by the molecular dynamics simulations. These studies provided five key insights into the PITPα lipid exchange cycle: (i) interaction of PITPα with the membrane is spontaneous and mediated by four specific protein substructures; (ii) the ability of PITPα to initiate closure around the PtdCho ligand is accompanied by loss of flexibility of two helix/loop regions, as well as of the C-terminal helix; (iii) the energy barrier of phospholipid extraction from the membrane is lowered by a network of hydrogen bonds between the lipid molecule and PITPα; (iv) the trajectory of PtdIns or PtdCho into and through the lipid-binding pocket is chaperoned by sets of PITPα residues conserved throughout the StART-like PITP family; and (v) conformational transitions in the C-terminal helix have specific functional involvements in PtdIns transfer activity. Taken together, these findings provide the first mechanistic description of key aspects of the PITPα PtdIns/PtdCho exchange cycle and offer a rationale for the high conservation of particular sets of residues across evolutionarily distant members of the metazoan StART-like PITP family.